(535) Computer Application to the Solution of Inventory Methods - Deterministic Models تطبيق الحاسوب لحل طرق الجرد - النماذج الحتمية - Mohamed A. Mongi (معهد التخطيط القومي, 2026)
This study aims to illustrate how computers are used in solving inventory models, with the TRA language employed to code these models for the IBM 1620 computer. The problem at hand is to determine the optimal quantity of goods to be stocked to meet the expected demand over a specific period. The goal is to determine the inventory level that minimizes the total costs associated with the situation. The costs are categorized into two types: holding costs and penalty costs, which arise when the stock on hand does not meet the demand. The models are solved based on either deterministic or probabilistic demand. This paper will focus on deterministic models, with probabilistic cases to be discussed in a later paper